2010
DOI: 10.3113/fai.2010.0229
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Stability of Intramedullary Technique for Fixation of Joint Depressed Calcaneus Fracture

Abstract: This fixation technique provides a biomechanically stable construct with the potential for a minimally invasive approach and improved post-operative soft tissue healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 17 publications
0
12
0
4
Order By: Relevance
“…In this study, the construct stability of LPF was greater than that of the two crossing screws; it had the smallest displacements at the fracture gaps. Other studies (Nelson et al, 2010;Smerek et al, 2008) found similar results, where LPF of calcaneal fractures provided better fracture reduction than fixation with percutaneous screws. However, this high rigidity promoted a higher concentration of stress on the implant, which, in this situation, could result in hardware failure.…”
Section: Discussionmentioning
confidence: 56%
“…In this study, the construct stability of LPF was greater than that of the two crossing screws; it had the smallest displacements at the fracture gaps. Other studies (Nelson et al, 2010;Smerek et al, 2008) found similar results, where LPF of calcaneal fractures provided better fracture reduction than fixation with percutaneous screws. However, this high rigidity promoted a higher concentration of stress on the implant, which, in this situation, could result in hardware failure.…”
Section: Discussionmentioning
confidence: 56%
“…22,28 To enhance stability, additional lateral plate fixation, contoured along the posterior facet, was used in the present study. 18 The significant improvement in Bohler's angle in the present study indicated that percutaneous reduction via the sinus tarsi approach allowed for adequate restoration of calcaneal height.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the specific fracture type, one or two more screws were directed cranially toward the posteromedial and posterolateral fragments, fixing these to the tuberosity fragment and serving as additional support for the posterior facet ( Figure 3B and 3C). 22 No bone graft was used in any patient. In the case of a comminuted anterior process fracture, fixation with an additional small plate or screws was considered.…”
Section: Operative Proceduresmentioning
confidence: 99%
“…However, the fixation using plates has the disadvantages of greater soft tissue injury than the percutaneous method and weak fixation strength due to the use of small plates and 2.7-mm screws. According to a recent biomechanical study, two cannulated screws to the medullary cavity shows same to better biomechanical strength than plates 34. In the present study, Steinmann pins were used to fix anterior and posterior bone fragments in the first eight cases and we have experienced collapse of Böhler's angle in some cases.…”
Section: Discussionmentioning
confidence: 70%
“…Fixation using Steinmann pins is simple surgically, but the fixation strength achieved is weak and their use is accompanied by the risk of pin site infection. Cannulated screws of diameter of 6.5 or 7 mm are more commonly used and have been reported to have satisfactory fixation strength 34. Recently, the fixation using plates has prodeuced better results with the development of low-profile plates 18.…”
Section: Discussionmentioning
confidence: 99%